The Family Court: Some Socio-Legal Implications - William M. Kephart (Washington University Law Quarterly, 1955)
While the family court movement is relatively new compared to that of the juvenile court, there are both operational and, more important, conceptual similarities between the two courts. As a matter of fact, the jurisdiction of juvenile courts in some areas has been extended to include parents as well as children, and it was this extension of jurisdictional authority which was one of the factors leading to the development of the integrated family court. In the following analysis the implications of this philosophical parallelism between the two courts will, I hope, become apparent.
Keywords: Courts – United States; Sociology